Evaluation of Quercetin Content, Colour and Selected Physico-Chemical Quality Parameters of Croatian Blackberry Wines - Klarić Daniela Amidžić; Klarić Ilija; Velić Darko; Velić Natalija; Marček Tihana (Polish Journal of Food and Nutrition Sciences)
Blackberry wine, the most widespread Croatian fruit wine, is produced by yeast fermentation of raw blackberry juice or must. Even though the production and intake of blackberry wine in Croatia has been increasing for years, the available data on the overall quality and blackberry wine composition is still scarce. The objective of this work was to evaluate the quercetin content, colour and selected physico-chemical quality parameters of 15 Croatian blackberry wine samples, divided into two groups denominated as CWB and OWB regarding the blackberries’ cultivation type (conventional and organic). The quercetin content ranged from 0.81 to 21.67 mg/L (average: 6.16 mg/L, median 3.96 mg/L) and was consistent with some published studies. Compared to CBW group, quercetin content of OBW samples seemed to be more balanced and slightly higher (OBW median: 3.99 mg/L, CWB median: 1.80 mg/L). The presence of cyanidin and pelargonidin (as aglycons) was detected in very low concentrations in four and seven samples, respectively. Determination of the colour revealed that the most important component contributing to colour intensity was yellow (51 %), followed by red (40 %). The chemical quality parameters were in accordance with the available published results on blackberry and grape wines and were as follows: relative density 1.0017–1.0660 g/mL, concentration of reducing sugars 13.5–177.6 g/L, alcoholic strength 9.37–14.78% vol, pH 3.11–3.56, total acidity 6.7–18.1 g/L, ash 1.59–4.11 g/L, alkalinity of ash 1.54–3.79 g/L, total nitrogen 65.50–361.15 mg/L, and total phosphorus 32.03–118.53 mg/L. No significant overall differences were noticed between the conventional and organic group of samples.